The effectiveness of promoting health literacy through infographics combined with health behavior counseling for type 2 diabetes patients in Nakhon Nayok Province, Thailand - Panyasaisophon, Thanakorn; Visuttranukul, Ammara; Prommala, Prombuncha; Thamrongworakun, Phitsaran (Edelweiss Applied Science and Technology, 2026)
This study aimed to examine the effects of a health literacy promotion program using infographics combined with health behavior counseling among patients with type 2 diabetes in Nakhon Nayok Province, Thailand. A quasi-experimental, one-group pretest–posttest design was used with 30 purposively selected patients. The intervention consisted of a health literacy program integrating infographics and health behavior counseling. Data were collected using health literacy and health behavior questionnaires and glycated hemoglobin (HbA1c) measurements. Descriptive statistics and paired-sample t tests were used for data analysis. After the intervention, participants showed significant improvements in health literacy, including knowledge, access to healthcare services, communication skills, self-management, media literacy, and decision-making (p < 0.01). Health behaviors related to diet, physical activity, stress management, smoking and alcohol control, and medication adherence also improved significantly (p < 0.01). HbA1c levels significantly decreased after the intervention (p < 0.01). The use of infographics combined with health behavior counseling effectively enhanced health literacy, promoted healthy behaviors, and improved glycemic control. This program can be integrated into healthcare settings to strengthen diabetes self-management, improve health outcomes, and reduce the risk of diabetes-related complications.